Impact of Social Responsibility Dimensions on Achieving Sustainable Development Goals: A Qualitative Study on the Abu Dhabi Police Service - Mohammed A. Alawlaqi; Nehad I. Ineizeh; Umi Hamidaton Mohd Soffian Lee; Abdul Rahim Zumrah (International Institute for Science, Technology and Education, 2026)
Non-Indexed Publication